<p>Can anyone explain how to solve the following problems?</p>
<p>(x-1)^(log x-1 ) = 100(x-1)</p>
<p>log(base 2)X + log(base 4)X + log(base 8)X</p>
<p>Can anyone explain how to solve the following problems?</p>
<p>(x-1)^(log x-1 ) = 100(x-1)</p>
<p>log(base 2)X + log(base 4)X + log(base 8)X</p>
<h1>1: First log both sides to get rid of the exponent, which should give you:</h1>
<p>[log(x-1)]^2 = log[100(x-1)] = log(100) + log(x-1) = 2 + log(x-1)</p>
<p>Let a = log(x-1)</p>
<p>a^2 - a - 2 = 0
(a-2)(a+1) = 0</p>
<p>Resubstitute in log(x-1) and solve.</p>